Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.3 Complex Numbers - 1.3 Exercises: 8

Answer

true

Work Step by Step

Note that $i^{12}=(i^2)^6$. Thus, the given expression is equivalent to: $=(i^2)^{6}$ With $i-\sqrt{-1}$. the expression above simplifies to: $=[(\sqrt{-1})^2]^6 \\=(-1)^6 \\=1$ Therefore the given statement is true.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.